1974
DOI: 10.1080/00268977400101491
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo calculations of reaction rates and energy distributions among reaction products, F+D2→DF+D

Abstract: A three-dimensional classical trajectory analysis is used to determine the reaction dynamics of the reaction F + D2(v, J) -+DF(v', J') + D on an assumed London-Eyring-Polanyi-Sato (LEPS) potential energy surface. Monte Carlo procedures are used to start each collision trajectory. An analysis is presented of the dependences of the total reaction cross sections ar and specific reaction cross sections a(v, J, v', E1Q on the relative translational energy and initial vibrational and rotational energy of the reagent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…6 The rate constants used in the present study are those reported in Ref. 7, except that the V-T deactivations of DF by D and HF are increased by 30 times and 3 times, respectively.…”
Section: Simplified Model Of Lasing Mediummentioning
confidence: 96%
See 3 more Smart Citations
“…6 The rate constants used in the present study are those reported in Ref. 7, except that the V-T deactivations of DF by D and HF are increased by 30 times and 3 times, respectively.…”
Section: Simplified Model Of Lasing Mediummentioning
confidence: 96%
“…where g is the average gain coefficient over a half-nozzle pair, L G the total gain length, I' 3 and I' 6 the flux density going to the gain sheet, and I 6 and I 3 the flux density coming out from the gain sheet (see Fig. 1).…”
Section: Simplified Model Of Radiation Field-lasing Medium Interactionmentioning
confidence: 99%
See 2 more Smart Citations